Números transcendentes - Carvalho, Wagner Wilson Pereira de (2018)
In this work, we study algebric and transcendent numbers in the context of real numbers. By some results, concerning the enumerability concept we show an evidence of the existence of transcendental numbers proposed by Cantor. Besides, we present the Liouville’s constant deﬁnition and show that it is a transcendent number. We ﬁnish by bringing up some aspects of the numerical sets and the elementary operations deﬁned in those sets, detaching the importance of the way those concepts should be treated in the Basic Education.